2021
DOI: 10.1002/esp.5143
|View full text |Cite
|
Sign up to set email alerts
|

Seepage mechanisms and permeability differences between loess and paleosols in the critical zone of the Loess Plateau

Abstract: The soil in the Loess Plateau has special permeability characteristics due to the alternating distribution of loess and paleosol layers. Using an analysis of the physical properties, microstructure and thermogravimetric analysis of loess and paleosol, this paper examines strata seepage mechanisms in the loess tableland area and considers the applicability of a hydraulic conductivity empirical formula. The analysis shows that hydraulic conductivity attenuation with depth can be represented by a negative exponen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 83 publications
(139 reference statements)
0
2
0
Order By: Relevance
“…Water is a key factor that induces landslides in the loess area due to the loess's water sensitivity; however, the complexity of the loess structure and its properties result in the diversity and uncertainty of the water infiltration within the loess 9 , 45 – 47 . Many scholars have researched water infiltration problems within loess 26 , 46 , 48 50 . Some researchers believe that rainfall recharges the groundwater through dominant infiltration channels within the loess, such as vertical joints, tensile cracks, and sinkholes 26 , 46 , 51 53 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Water is a key factor that induces landslides in the loess area due to the loess's water sensitivity; however, the complexity of the loess structure and its properties result in the diversity and uncertainty of the water infiltration within the loess 9 , 45 – 47 . Many scholars have researched water infiltration problems within loess 26 , 46 , 48 50 . Some researchers believe that rainfall recharges the groundwater through dominant infiltration channels within the loess, such as vertical joints, tensile cracks, and sinkholes 26 , 46 , 51 53 .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous research results found two types of infiltration in the loess 26 , 28 , 33 , 49 . One type is the unsaturated seepage from the surface to the underground 50 , 51 . Although the short-term infiltration depth is limited, the long-term unsaturated infiltration can recharge the groundwater.…”
Section: Discussionmentioning
confidence: 99%